2013
DOI: 10.1016/j.rmed.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure induces acutely airway acidification and oxidative stress

Abstract: Previous studies have shown that secondhand smoke induces lung function impairment and increases proinflammatory cytokines. The aim of the present study was to evaluate the acute effects of secondhand smoke on airway acidification and airway oxidative stress in never-smokers. In a randomized controlled cross-over trial, 18 young healthy never-smokers were assessed at baseline and 0, 30, 60, 120, 180 and 240 min after one-hour secondhand smoke exposure at bar/restaurant levels. Exhaled NO and CO measurements, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Previous studies have not reported consistent associations between ETS exposure and oxidative stress biomarkers measured in EBC. After a 1h experimental exposure to ETS, healthy young adults had significantly higher levels of H 2 O 2 in EBC (Kostikas et al, 2013). In another study, healthy children who had one or two parents who were smokers did not have significantly higher levels of H 2 O 2 in EBC when compared to children who were not exposed to ETS (Doniec et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have not reported consistent associations between ETS exposure and oxidative stress biomarkers measured in EBC. After a 1h experimental exposure to ETS, healthy young adults had significantly higher levels of H 2 O 2 in EBC (Kostikas et al, 2013). In another study, healthy children who had one or two parents who were smokers did not have significantly higher levels of H 2 O 2 in EBC when compared to children who were not exposed to ETS (Doniec et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial variability and temporality have been shown to be significant predictors of BC concentrations in NYC, stressing the importance of understanding local exposure patterns (Clougherty et al, 2013). Therefore, we sought to characterize the association between short-term domestic measures of BC, and additionally PM 2.5 and environmental tobacco smoke (ETS), another known pollutant associated with oxidative stress (Kostikas et al, 2013; Noakes et al, 2007) and 8-isoprostane measured in EBC as a surrogate marker of oxidative stress in a cohort of children living in NYC. We hypothesized that increased levels of all three of these measures of pollutant exposure would be associated with increased levels of 8-isoprostane in EBC.…”
Section: Introductionmentioning
confidence: 99%
“…In the 15 non-smokers, percentage flow-mediated vasodilation decreased and plasma 8-isoprostane increased significantly to concentrations comparable to those of the active smokers. Kostikas et al undertook a randomised controlled cross-over trial in which they exposed 18 never smokers to bar/restaurant levels of ETS for one hour [18]. Following exposure, H 2 O 2 in the exhaled breath condensate increased and remained significantly higher four hours after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a 103 larger study and the procedures followed are described in detail elsewhere (Flouris et al, 2013). 104…”
Section: Study Design and Procedures 99mentioning
confidence: 99%
“…The specific e-cigarette and liquid was selected for the study due 114 to the fact that this liquid was the only one in Greece that had been previously analyzed by an 115 independent publicly-funded Research Institute and consisted of >60% propylene glycol, <10% nicotine, 116 <5% linalool, <5% tobacco essence and <1% methyl vanilyn (Leondiadis, 2009) Non-smokers underwent a control session (PS CON ), a passive tobacco cigarette smoking session (PS TOB ) 124 and a passive e-cigarette smoking session (PS E-CIG ). Blood samples were collected prior to, immediately 125 after, as well as one hour after the smoking sessions, as previously described (Flouris et al, 2013). 126…”
Section: Active Smokers 106mentioning
confidence: 99%